(untitled) (Web of Teachers: Inderscience Research, 2023)
The article introduces primary school students to the expressive features and facets of the meaning of metaphors used in narrative texts. There was also a scientific study of aspects demonstrating the unique expressive capabilities and skill of the writer. The pragmatic possibilities of productive use of metaphor in literary texts, especially in works of the great epic genre, have been studied lyrically.